Community-Based Findings of Magnitude of Type 2 Diabetes Mellitus among Adults in Selected Towns of Western Ethiopia - Bikila Regassa Feyisa; Getu Mosisa; Bayise Biru; Sidise Debelo; Mebrate Dufera (Dubai Diabetes and Endocrinology Journal)
Background: The risk of diabetes mellitus (DM) is remarkably increasing globally, and it is alarmingly increasing in developing countries including Ethiopia, especially in urban residents. The present study was aimed at uncovering the magnitude of type 2 DM (T2DM) among adults residing in the selected towns of western part of Ethiopia. Methods: A community-based cross-sectional study design was conducted in towns of western Ethiopia from June 1 to June 30, 2019. Multistage and systematic random sampling techniques were employed. The data were collected using structured interviewer-administered questionnaire based on the World Health Organization STEPwise approach. Data were entered into EpiData 3.1, cleaned, and analyzed by the statistical package for social sciences software version 24. Descriptive statistics and logistic regression were used for the analysis. Results: The prevalence of T2DM was 7.0% (95% confidence interval [CI] 5.4–8.8) with 8.5% (95% CI 5.6–11.0) and 6.0% (95% CI 3.9–8.1) among males and females, respectively. Being married (AOR = 4.0, 95% CI 1.1–14.7) and divorced (AOR = 6.2, 95% CI 1.1–34.4), consumption of inadequate fruits and vegetables per day (AOR = 2.8, 95% CI 1.1–6.8), physical inactivity (AOR = 5.0, 95% CI 2.5–10.0), hypertension (AOR = 2.9, 95% CI 1.3–6.2), overweight (AOR = 2.3, 95% CI 1.1–4.9), and obesity (AOR = 19, 95% CI 4.5–50.1) were factors independently associated with T2DM. Conclusion: The prevalence of DM in the study area was found to be substantially higher than the national prevalence and other pocket studies in the country. Sociodemography and modifiable risk factors were affecting the prevalence of DM.